2019
DOI: 10.1162/asep_a_00659
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financialization and Financial Development on Inequality:  Panel Cointegration Results Using OECD Data

Abstract: This study compares the long-run impact of financialization and financial development on inequality through the panel cointegration approach using OECD country data. Results show that financialization, especially high-dividend tendency in non-financial corporations, is one of the causes of rising inequality measured as the share of the top 10 percent richest. Other measures of financialization, such as the increasing size of the financial sector and financial globalization, are not robustly linked to inequalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…If these challenges become permanent features of South Korea, 24 A firm-level analysis by Kim and Cho (2008) confirms this negative linkage from more foreign share to less investment. Shin and Lee (2019) confirm the positive linkages from more dividends payment to more inequality measured by the income share of the top 10% richest.…”
Section: The Korean Experience: From Short To Long Cyclessupporting
confidence: 57%
“…If these challenges become permanent features of South Korea, 24 A firm-level analysis by Kim and Cho (2008) confirms this negative linkage from more foreign share to less investment. Shin and Lee (2019) confirm the positive linkages from more dividends payment to more inequality measured by the income share of the top 10% richest.…”
Section: The Korean Experience: From Short To Long Cyclessupporting
confidence: 57%
“…The latter analysed the subject from two different scopes based on their research contexts. By employing panel data on the countries the effect of financial development on income inequality was examined by scholars such as Clarke et al (2006), Shabaz and Islam (2011), Jauch and Watzka (2015), De Haan and Sturm (2017), Younsi and Bechtini (2018), Shin and Lee (2019). On the other hand, Shahbaz et.…”
Section: Related Workmentioning
confidence: 99%
“…The aforementioned symptom associated with financialization is also one of the sources of the increasing income inequality, apart from the impacts of the skill-biased technological change including automation. H. Shin and K. Lee (2019) showed that the increased shares of stockholders in profits or financial resources of nonfinancial sectors led to the rising inequality measured by the income share of the top 10% rich in OECD countries, which includes Korea (Fig. 3).…”
Section: Corporate Governance Ownership and Financializationmentioning
confidence: 99%